Identificação de gene de reistência ao Colletotrichum lindemuthianum na cultivar andina de feijão comum Paloma - Castro, Sandra Aparecida de Lima (2014)
Anthracnose, caused by Colletotrichumlindemuthianum, is one of the most important leaf diseases of the common bean (Phaseolusvulgaris L.) and genetic resistance is the most effective method to control this disease. To date, 20 resistance genes have been characterized, of which nine are Andean. Thus, the search for new sources of Andean resistance is necessary. Therefore, the study aimed to characterize the genetic resistance of Andean cultivar Paloma, through inheritance and allelism tests and also molecular analysis. Inheritance tests were conducted in F2 populations of crosses between the cultivars Paloma (resistant) and Cornell 49-242 (susceptible), with races 73 and 2047 of C.lindemuthianum. The allelism tests were performed on 16 F2 populations derived from crosses between Paloma (R) and cultivars (R) with previously characterized genes using the races 65, 73 and 2047 of the pathogen. Visual assessment of symptoms was performed ten days after inoculation using a scale of 1 to 9. Genetic analysis of F2 population were performed using the chisquare test (?²). Molecular analysis in parental Paloma (R) and Michelite (R) was performed using RAPD marker AZ04. Inheritance tests indicated the presence of a dominant resistance gene in Paloma. Allelism tests showed that this gene present in Paloma is independent of the genes and allelesCo-1, Co-2, Co-34, Co-35, Co 4, Co-42, Co-43, Co-5, Co 6, Co-12, Co-13, Co-14, Co-15 and Co-16. Likewise, molecular analysis revealed that this gene present in Paloma is independent of Co-11 gene. The cultivar Paloma has proved to be a major source of resistance to anthracnose because it has a new Andean gene that allows its use in breeding programs of common beans. Thus, the authors propose the Co-20 symbol to name the gene present in the cultivar Paloma.